Comparison of National Growth Standards for Turkish Infants and Children with World Health Organization Growth Standards - Rüveyde Bundak; Zehra Yavaş Abalı; Andrzej Furman; Feyza Darendeliler; Gülbin Gökçay; Firdevs Baş; Hülya Günöz; Olcay Neyzi (Galenos Yayincilik, 2022)
INTRODUCTION: Using World Health Organization (WHO) standards in pediatric practice is still controversial in many countries. It is suggested that national growth charts best reflect the genetic and ethnic characteristics of a population. The aim of this study was to compare length/height, body weight, and body mass index (BMI) in healthy Turkish children of ages 0 to 18 with those proposed by WHO as the international growth standards. METHODS: The data of Turkish children were collected from infant/child population aged 0-5 years (2391 boys, 2102 girls) and children of ages between 6-18 years (1100 boys, 1020 girls). For comparison, the 50th, 3rd, and 97th percentile curves for length/height, weight, and BMI in Turkish children were plotted together with respective WHO data. RESULTS: Heights were essentially similar in the Turkish and WHO data at ages between 3-10 years. Turkish children were markedly taller compared to the WHO standards after the age of 10 years. Evaluation of the 3rd percentile data revealed that Turkish boys were shorter than the WHO subjects in the first 2 years of life. From 6 months of age, Turkish children showed higher weight for age values in the 3rd, 50th, and 97th percentiles. In all age groups between 6 months and 3 years, and in between 6-18 years of age, Z-score values, as well as the 50th, 15th, 85th, and 95th percentile values were higher in Turkish children. The differences were particularly noteworthy at ages 1-2 years and in the pubertal years. DISCUSSION AND CONCLUSION: WHO growth standards do not reflect the growth of Turkish children and may substantially alter the prevalence of short stature and underweight in Turkish children in the 0-5 years age group. When assessing the nutritional and growth status of children, national growth standards may be more appropriate.